ORIGINAL RESEARCH - Vivcharyk, N. M. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Word, 2022)
The playwriting of Mykola Kostomarov occupies an important place in the national artistic heritage, because it played an important role not only in the literary process of the 30s and 40s of the 19th century, but also in the development of theatrical culture. Taking into account the work of her predecessors, in particular Vasyl Ivashkiv, Mark Pavlyshyn, Valeriya Smilyanska, Agapiy Shamray, Mykhailo Yatsenko, Olga Tovt consciously chose dramaturgy as one of the least studied layers of M. Kostomarov's creative output as the object of her research. The monographic work of Olga Tovt, candidate of philological sciences from the Uzhhorod National University, is a successful attempt to fill the gaps caused by the deliberate tabooing of "unpleasant" historical topics during the Soviet period.